Social work interventions in the psycho-social management of stress among industrial workers (2008)
The paper described the nature of stress and how it affects workers' health and job performance in industrial organizations. The paper pointed out that, stress can cause physical and mental illness in the workers and these can affect their performance at work negatively. It also discussed how social work interventions are helpful in the psycho-social management of stress among industrial workers. it is suggested in this paper that, the employers of labour should help in meeting the needs of workers adequately and should ensure that good interpersonal relationship exist between them and their employees to help them experience reduced symptoms of stress and anxiety that can cripple them at work.